PKM Sosialisasi Pembentukan Karakter Peserta Didik Melalui Model Pembelajaran Proyek Base Learning Pada Mata Pelajaran Matematika Di SMA Kota Batam - Hizmi Wardani; Nelvitia Purba; Christiani Prasetyasari; Herlina Suciati; Wilda Fasim Hasibuan; Zawahir Nafsah; Dormauli Manurung (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
PKM is carried out at Nabilah Islamic High School Batam. This program is carried out in partnership between the Al-Washliyah Muslim Nusantara University (UMN) PKM Team and the Batam University PKM Team with activities including: Preliminary Stage, at this stage, the service team takes care of the letters of permission and correspondence from UMN Al Washliyah Medan to survey carrying out this community service activity. (2) Implementation stage, at this stage, the socialization of students' character formation is carried out through the base learning project learning model in mathematics subjects from UMN Al Washliyah Medan using PowerPoint. In this socialization activity, lectures and questions and answers are carried out, so that the activity will achieve the results and targets as expected and (3) Evaluation Stage, at this stage an evaluation is carried out by making a questionnaire before and after the implementation of PKM activities at Nabilah Islamic High School Batam, to find out there is an increase in understanding regarding Mathematics lessons. The PKM results concluded that the application of the Project-Based Learning learning model in mathematics learning can improve students' character values. This is evidenced by the average percentage of character values ​​indicator scores of 64% before PBL socialization and 81% after PBL socialization. Therefore, this PBL learning model can be applied to improve character values ​​based on student responses after PKM activities are carried out